Investigación y desarrollo, innovación y productividad: un análisis econométrico a nivel de la firma - Benavente, José Miguel (Estudios de Economía, 2016)
We expand the research line about how Research and Development affectsinnovation and productivity at a plant level in Chile (Benavente & Crespi, 1996,and Benavente, 2002). We find that R&D expenditures are highly persistent intime where firm size accurately predicts the amount of resources invested inthese activities. On the other hand, commercial success of new innovations arehighly dependent on R&D expenditures, plant size and the continuousobservation of new and innovative ideas generated both inside and outside theplant. Finally, mid run plant´s productivity is positively affected by technologicalinnovations introduced in the past and most important, if the plant receivedsome public support for its financing. Results show that for each subsided dollar,productivity rises, on average, equivalent to five dollars in value.